Media in church and mission communicating the Gospel - Sogaard, Viggo (Pasadena, CA William Carey Library, 1993)
Includes bibliographical references and index.
Keywords: Mass media -- religious aspects -- Christianity; Communication -- religious aspects -- Christianity